2021
DOI: 10.4103/jfmpc.jfmpc_1312_20
|View full text |Cite
|
Sign up to set email alerts
|

knowledge and utilization of family planning among rural postpartum women in Southwest Nigeria

Abstract: Background: In Nigeria, contraceptive use has remained low, 12% for any modern method, despite the huge resources committed to family planning programs by stakeholders. This study was carried out to assess the knowledge and utilization of family planning and determine predictors of utilization of family planning among postpartum women attending primary health care centers (PHCs) in a selected rural area of Lagos State, southwest Nigeria. Methods: This was a descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Only a small number of respondents engage in family planning more than six weeks after giving birth. The most frequently used methods are implants, injectables, and male condoms, which aligns with the findings reported by Ackerson and Zielinski (2017), Duru et al (2018), Joshi et al (2020), and Anate et al (2021).…”
Section: Discussion Of Findingssupporting
confidence: 89%
See 2 more Smart Citations
“…Only a small number of respondents engage in family planning more than six weeks after giving birth. The most frequently used methods are implants, injectables, and male condoms, which aligns with the findings reported by Ackerson and Zielinski (2017), Duru et al (2018), Joshi et al (2020), and Anate et al (2021).…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Nevertheless, in order to attain the expected reductions in fertility rates, it is imperative to persist in efforts towards gender parity and the empowerment of women. This can be achieved by enhancing male involvement in family planning, advocating for female education, eradicating all manifestations of violence and prejudice against women, abolishing early, coerced, and child marriages, and guaranteeing women's equal access to employment opportunities, social safeguards, and political engagement (Anate, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum contraception knowledge and practice remains low in the postpartum period [34][35][36][37]. Studies have shown a time lag of 5 months from resumption of sex and initiation of postpartum contraception use [38].…”
Section: Discussionmentioning
confidence: 99%